Mencegah Nomophobia Sejak Dini Melalui Layanan BK di MDTA Aek Badak Julu : Penelitian - Asmaryadi Habibi; Nurhasanah Pardede; Putoro Dongoran; Eny Mayasari; Fauzan Habibie Nasution; Devi Adriany; Mutiara Astari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Smartphone use has become an essential part of people's lives, including elementary school-aged children, due to the ease of access to information, entertainment, and communication in the digital era. However, early childhood should have the mental freedom to learn without dependence on digital media. This study used a qualitative descriptive method with data triangulation techniques through observation and unstructured interviews, as well as a Participatory Action Research (PAR) approach involving the madrasah principal and teachers. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the influence of technology remains strong in MDTA Aek Badak Julu, although not all students own mobile phones. Many students are exposed to parental mobile phone content and exhibit symptoms of addiction, including nomophobia. This dependence is influenced by a lack of parental supervision and the habit of giving mobile phones to children. Guidance and Counseling Services have proven effective in changing student behavior so that they better understand that mobile phones are not primary needs, even though the village environment strongly emphasizes religious education.